Early Retinal Flow Changes after Vitreoretinal Surgery in Idiopathic Epiretinal Membrane Using Swept Source Optical Coherence Tomography Angiography - Mastropasqua, Rodolfo; D’Aloisio, Rossella; Viggiano, Pasquale; Borrelli, Enrico; Iafigliola, Carla; Di Nicola, Marta; Aharrh-Gnama, Agbéanda; Di Marzio, Guido; Toto, Lisa; Mariotti, Cesare; Carpineto, Paolo (Journal of clinical medicine, 2019)
(1) Background: The aim of this observational cross-sectional work was to investigate early retinal vascular changes in patients undergoing idiopathic epiretinal membrane (iERM) surgery using swept source optical coherence tomography angiography (SS-OCTA); (2) Methods: 24 eyes of 24 patients who underwent vitrectomy with internal limiting membrane (ILM) peeling were evaluated pre- and postoperatively using SS-OCTA system (PLEX Elite 9000, Carl Zeiss Meditec Inc., Dublin, CA, USA). For each eye, five 6x6-mm OCTA volume scans were acquired by two observers independently. The en face images of superficial capillary plexus (SCP) were then exported to imageJ and a semi-automated algorithm was used for subsequent quantitative analysis. Perfusion density (PD), vessel length density (VLD), vessel diameter index (VDI) and vessel tortuosity (VT) of SCP were evaluated in both the parafoveal (2.5 mm diameter) and perifoveal areas (5.5 mm diameter); (3) Results: At OCTA analysis statistically significant differences were found between controls and diseased eyes for all parameters in parafoveal and perifoveal regions (p < 0.001; p < 0.05) except for perifoveal VLD. During 6-month follow up, both anatomical/perfusion and functional parameters showed a statistically significant improvement if compared to preoperative values. In detail, at one-month post vitrectomy, VLD and VT significantly changed in parafoveal region (p = 0.043; p = 0.045), while PD and VDI showed a trend of increase in both parafoveal and perifoveal region. At 6 months after surgery, PD, VLD and VT of parafoveal region significantly improved (p = 0.021, p = 0.018, p = 0.047 respectively). (4) Conclusions: SS-OCTA provides a quantitative and qualitative analysis of the superficial capillary plexus allowing for early vascular changes assessment after vitrectomy with iERM and ILM peeling.